Critical Success Factors in Selecting & Implementing Core Banking Systems in Local Commercial Banks in Sri Lanka - Hettiarachchi, Nishantha (My University, 2011)
Sri Lankan Licensed Commercial Banks are constantly investing on modern state-of-the-art technology in order to compete among themselves, compete with global banks, which have local presence, cater ever growing needs of their customers as well as to comply with complex regulatory requirements. Majority of the technology resources acquired by local Licensed Commercial Banks (LCBs) are of foreign origin, for which a vast sum of foreign exchange is spent. Therefore, it is imperative for the Sri Lankan economy as a whole and the individual banks that they succeed in their technology implementations, most importantly Core Banking System (CBS) projects, to achieve the desired organizational objectives and project outcomes. The main purpose of this study was to identify Critical Success Factors for CBS selection and implementation in Sri Lankan LCBs and to define a framework, which could be used by the LCBs to make their CBS projects successful. On evaluating some of the software selection and implementation models via a literature survey, the survey-based method was selected to analyze experiences in selection and implementation of CBS in the local LCBs. This was accomplished by identifying success factors related to IT and ERP projects based on literature survey. Through focus group interviews targeting top managers of LCBs additional success factors related to local context were identified while validating the relevance of success factors identified through the literature survey. The survey questionnaire was designed based on the literature and on the information collected through the interviews to collect data. The survey questionnaire was distributed among 598 individuals identified as sample population across 10 LCBs. Out of the 598 only 320 responded and responses of 244 CBS project experienced respondents were identified for further analysis. Following noteworthy findings were observed on analysis of survey data. Most of the respondents were of the view that improved efficiency and end user satisfaction was the most important project goal to achieve, related to CBS projects. Timely implementation or implementing within allocated budget, was not considered as important by the respondents. x Corporate Management and IT Departments respectively have been identified as the top most influencing factors in deciding on CBS. Out of the 23 success factors in the questionnaire, 16 have been identified as Critical Success Factors (CSFs). Out of the 16, six were related to the CBS selection process and 10 were related to the implementation process. There were three CSFs common to both selection and implementation processes. Out of the CSFs related to selection, preparation of proper requirements has been identified as the most critical success factor. In relation to the implementation, vendor support and commitment has been identified as the key factor. Further, the research outcome indicates that approximately 25% of the CBS implementations have failed to meeting the project goals and objectives. When evaluated against the two important project success measurement criteria of implementing within the anticipated period and being within the project budgets, then failure rate would be well above 25%. Based on the identified CSFs, a framework for CBS projects has been developed and a comprehensive set of guidelines have been proposed for the Sri Lankan LCBs, which could be useful for these banks in their future CBS Projects.